Dynamic Compaction for Treating Millions of Square Meters of Sand - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (Australian Geomechanics Society, 2011)
To the knowledge of the authors, the 4.84 million square meter ground improvement project of Al Falah Community Development in Abu Dhabi is the physically largest single contract that has ever been undertaken by a specialist ground improvement contractor. The peak ground improvement production rate of 966,000 m2 per month also appears to be a new world record. This paper will describe the initial ground conditions of the project, the development of a foundation solution based on the utilization of ground improvement technology and the account of how mobilization, execution of Dynamic Compaction for the treatment of loose desert sands and verification testing by the Menard Pressuremeter Test were all realized within a mere period of 7 months.